Heat-Shock Promoters: Targets for Evolution by P Transposable Elements in Drosophila - Walser, Jean-Claude (Public Library of Science, 2006)

(untitled)
Transposable elements are potent agents of genomic change during evolution, but require access to chromatin for insertion—and not all genes provide equivalent access. To test whether the regulatory features of heat-shock genes render their proximal promoters especially susceptible to the insertion of transposable elements in nature, we conducted an unbiased screen of the proximal promoters of 18 heat-shock genes in 48 natural populations of Drosophila. More than 200 distinctive transposable elements had inserted into these promoters; greater than 96% are P elements. By contrast, few or no P element insertions segregate in natural populations in a “negative control” set of proximal promoters lacking the distinctive regulatory features of heat-shock genes. P element transpositions into these same genes during laboratory mutagenesis recapitulate these findings. The natural P element insertions cluster in specific sites in the promoters, with up to eight populations exhibiting P element insertions at the same position; laboratory insertions are into similar sites. By contrast, a “positive control” set of promoters resembling heat-shock promoters in regulatory features harbors few P element insertions in nature, but many insertions after experimental transposition in the laboratory. We conclude that the distinctive regulatory features that typify heat-shock genes (in Drosophila) are especially prone to mutagenesis via P elements in nature. Thus in nature, P elements create significant and distinctive variation in heat-shock genes, upon which evolutionary processes may act.